Performance and age of African and non-African runners in half- and full marathons held in Switzerland, 2000-2010 - Aschmann, A.; Knechtle, B.; Cribari, M.; Rüst, C. A.; Onywera, V.; Rosemann, T.; Lepers, R. (Open Access Journal of Sports Medicine, 2013)
Endurance running performance of African (AF) and non-African (NAF) athletes is investigated, with better performances seen for Africans. To date, no study has compared the age of peak performance between AF and NAF runners. The present research is an analysis of the age and running performance of top AF and NAF athletes, using the hypothesis that AF athletes were younger and faster than NAF athletes. Methods: Age and performance of male and female AF and NAF athletes in half-marathons and marathons held in Switzerland in 2000-2010 were investigated using single and multilevel hierarchical regression analyses. Results: For half-marathons, male NAF runners were older than male AF runners (P = 0.02; NAF, 31.1 years ± 6.4 years versus AF, 26.2 years ± 4.9 years), and their running time was longer (P = 0.02; NAF, 65.3 minutes ± 1.7 minutes versus AF, 64.1 minutes ± 0.9 minutes). In marathons, differences between NAF and AF male runners in age (NAF, 33.0 years ± 4.8 years versus AF, 28.6 years ± 3.8 years; P < 0.01) and running time (NAF, 139.5 minutes ± 5.6 minutes versus AF, 133.3 minutes ± 2.7 minutes; P < 0.01) were more pronounced. There was no difference in age (NAF, 31.0 years ± 7.0 years versus AF, 26.7 years ± 6.0 years; P > 0.05) or running time (NAF, 75.0 minutes ± 3.7 minutes versus AF, 75.6 minutes ± 5.3 minutes; P > 0.05) between NAF and AF female half-marathoners. For marathoners, NAF women were older than AF female runners (P = 0.03; NAF, 31.6 years ± 4.8 years versus AF, 27.8 years ± 5.3 years), but their running times were similar (NAF, 162.4 minutes ± 7.2 minutes versus AF, 163.0 minutes ± 7.0 minutes; P > 0.05). Conclusion: In Switzerland, the best AF male half-marathoners and marathoners were younger and faster than the NAF counterpart runners. In contrast to the results seen in men, AF and NAF female runners had similar performances. Future studies need to investigate performance and age of AF and NAF marathoners in the World Marathon Majors Series.